An optimized method for retrograde labelling and quantification of rabbit retinal ganglion cells. (April 2023) - Wang, Qilin; Lin, Xingyan; Wang, Juanjuan
Abstract: Rabbits are a commonly used animal model in glaucoma research, but their application has been limited by the techniques used to assess optic nerve injury (ONI). Our study devised an optimized method for retrograde labelling and analysing rabbit retinal ganglion cells (RGCs). This method involved improvements over the conventional method regarding the stereotaxic device, the positioning of superior colliculi, the target of axonal tracer delivery, and the visualization and analysis of labelled RGCs. To evaluate its efficacy, eight New Zealand White rabbits were divided into naïve and ONI groups. Unilateral limbal buckling surgery was performed in each animal of the ONI group to induce chronic ocular hypertension (OHT). The animals of both groups were injected with indocyanine green (ICG) into the interstice between the superior colliculus and occipital lobe on each side of the brain, and their eyes were examined by confocal scanning laser ophthalmoscopy (CSLO) after 48 h. The acquired images were then analysed to quantify the number of ICG-labelled RGCs in these eyes and their loss induced by OHT. To verify the identity and changes of the labelled RGCs, the retinas of the rabbits were subjected to immunofluorescence analyses. In addition, three animals were subjected to a second ICG labelling after 12 months to determine the influence of this procedure on the long-term viability of the labelled RGCs. Our results showed that ICG-labelled RGCs were detected by CSLO throughout the retinas of all animals. These RGCs showed a distinctly higher density below the ONH and were defective in sectorial areas in OHT eyes. Their average number in the cell counting area was 3989.2 ± 414.2 and 4023.3 ± 603.4 in the right and left eyes, respectively, of the naïve animals and 2590.9 ± 1474.2 and 3966.7 ± 24.0 in the OHT and non-OHT eyes, respectively, of the ONI animals. Immunofluorescence analyses showed positive staining with Brn3a and RBPMS in the ICG-labelled RGCs and sectorial defects of the cells in the OHT eyes, similarly as observed by CSLO. The second ICG labelling after 12 months in three animals showed no appreciable changes in RGC density compared with the first one. In summary, the optimized method of rabbit RGC retrograde labelling is reliable and accurate in both naïve and ONI animals and offers an approach for longitudinal observation of RGCs in the same eyes, which suggests its potential as a powerful tool for glaucoma and optic nerve research. Highlights: Rabbit retinal ganglion cells are consistently back labelled with indocyanine green. Rabbit optic nerve injury was evaluated in vivo by quantifying retinal ganglion cells. Indocyanine green has minimal influence on rabbit retinal ganglion cell viability.